Tragédia como criação, colheita, e festa em “Assim falou Zaratustra” - Novo, Jean Carlos Cavalcante (2022)
Our research proposes an investigation about Nietzsche’s tragic philosophy from concepts as creation, harvest, and rejoice, wrote in “Prologue” of “Thus Spake zarathustra”. We develop an interpretation of Nietzsche’s philosophy that recognize an intrinsic relation between art and metaphisical criticism approaching us to the phenomenological hermeneutics philosophers form XX century. We argue that hervest and rejoice are both fundamental elements of the complex process of artistical creation, characterized as an ontological comprehension of time and language, aiming a wide comprehension of tragic phenomena. Our interpretative lecture focus on each of four books that composes Zarathustra, paying a special attention to “Reading and writting”, “The great-longing”, “The vision and the enigma”, and “Noon-tide” discourses. Innitialy we propose a interpretation of the simbolic elements in “Prologue” in order to develop the proper meanning of creation, harvest, and rejoice, associating to other important concepts in Nietzsche’s philosophy as Will to Power, nihilism, and transvaluation. “Thus Spake Zarathustra” is the highest affirmation of a tragic way of thinking, and we notice its influence over philosophers as Gadamer and Heidegger, both share a common interest in problems related to time and language concerning to artistical creation phenomena.